Protein Ontology Project: 2006 updates - Sidhu, Amandeep; Dillon, Tharam S.; Sidhu, B.; Chang, Elizabeth (WIT Press, 2006)
Protein Ontology (PO) is a means of formalizing protein data and knowledge; protein ontology includes concepts or terms relevant to the domain, definitions of concepts, and defined relationships between the concepts. PO integrates protein data formats and provides a structured and unified vocabulary to represent protein synthesis concepts. PO provides integration of heterogeneous protein and biological data sources. This paper discusses the updates that happened to the Protein Ontology Project since it was last presented at the Data Mining 2005 Conference.